Mueve la burra, mueve la princesa: Algunos sinónimos de abortar en textos literarios y documentos auriseculares - Sanz-Lázaro, Fernando (Avisos de Viena, 2024)
The text explores the semantic evolution and connotations of the terms abortar, malparir, and mover in Spanish. Initially used in medical contexts, aborto and malparto describe specific stages or outcomes of pregnancy. Over time, malparido acquired pejorative connotations, denoting a person of low moral character or social status. The progression from medical to figurative usage reflects societal attitudes toward childbirth, morality, and language. The analysis considers historical texts, dictionaries, and literary examples to trace these shifts in meaning. The study highlights how language reflects and shapes cultural perceptions, illustrating the complex interplay between semantics, social norms, and linguistic evolution.